Web application development with R using Shiny : integrate the power of R with the simplicity of Shiny to deliver cutting-edge analytics over the Web /: integrate the power of R with the simplicity of Shiny to deliver cutting-edge analytics over the Web. (2016) - Beeley, Chris
No abstract available